Discipline al lavoro. Sull’ambiguità del ruolo dell’antropologo nell’accoglienza italiana - Sbriccoli, Tommaso (Antropologia Pubblica, 2017)
In recent years, we have been witnessing an increasing involvement of anthropologists as workers within the Italian system of shelter for asylum seekers and refugees. Such involvement deserves to be investigated for many reasons. On one side, it illustrates what role and function society at large believes anthropology should take on. On the other side, it also makes explicit what role and competences anthropologists themselves deem to be able to perform and deploy. At the same time, it also shows the complex relations that are produced – in the neo-liberal context of dismantling of public university and externalization of welfare services – between academia, market, civil society and institutions. Finally, such collaboration of our discipline with institutions governing Other’s life inevitably evokes past connections between anthropology and colonialism and consequently asks for a particularly sound analytical effort. In this article, I will thus delineate some areas of problematization of the roles of anthropologists within the area of administration of asylum seekers’ and refugees’ lives. I will thus shade light on the discursive and institutional devices operating in such field, showing how the knowledge and roles that anthropologists respectively deploy and enact work, or might work, in a twofold direction. On one side, in fact, they further structure the field in which they are inserted. On the other side, they can trigger what Lotman defines “explosive events”, by calling into question practices and models at work and pushing the contexts in which they are inserted towards unexpected reconfigurations.